The Effects of Atorvastatin on Global Cerebral Ischemia-Induced Neuronal Death - Kho, A Ra (Int J Mol Sci, 2021)
(1) Background and Purpose: Global cerebral ischemia-induced severe hypoxic brain damage is one of the main causes of mortality and long-term neurologic disability even after receiving early blood reperfusion. This study aimed to test the hypothesis that atorvastatin potentially has neuroprotective effects in global cerebral ischemia (GCI). (2) Methods: We performed two sets of experiments, analyzing acute (1-week) and chronic (4-week) treatments. For the vehicle (Veh) and statin treatments, 1 mL of 0.9% saline and 5 mg/kg of atorvastatin (ATOR) were administered orally. For histological analysis, we used the following staining protocols: Fluoro-Jade B and NeuN, 4-hydroxynonenal, CD11b and GFAP, IgG, SMI71, and vWF. Finally, we evaluated the cognitive function with a battery of behavioral tests. (3) Results: The GCI-ATOR group showed significantly reduced neuronal death, oxidative stress, inflammation, and BBB disruption compared with the GCI-Veh group. Moreover, the GCI-ATOR group showed decreased endothelial damage and VV proliferation and had significantly improved cognitive function compared with the GCI-Veh group in both models. (4) Conclusions: ATOR has neuroprotective effects and helps recover the cognitive function after GCI in rats. Therefore, administration of atorvastatin may be a therapeutic option in managing GCI after CA.